2020
DOI: 10.1002/jsfa.10732
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil from leaves of Eugenia calycina Cambes: Natural larvicidal against Aedes aegypti

Abstract: BACKGROUNDEugenia calycina is an endemic species in the Brazilian savannah (the Cerrado) and it is threatened with extinction. Several species of Eugenia are used as insecticides or insect repellents. No data are available on the larvicidal activity of E. calycina. The chemical composition of the essential oil (EO) from leaves of Eugenia calycina was analyzed by gas chromatography coupled to mass spectrometry (GC–MS) and the larvicidal activity against Aedes aegypti larvae in the third stage of development was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the work by Sousa, et al (2015), the oil from E. calycina leaves showed moderate cytotoxicity with CC50 137.4 μg/mL for HeLa cells, already in the work by Silva, et al (2021) showed an IC50 of 266.8 for HeLa cells, and an IC50 of 312.1 µg/mL for Vero cells within 24 h of exposure. Some oils have a toxic effect on MRC5 (human fibroblast) cells, such as oil from the leaves of E. flavescens DC.…”
Section: Goiás Minas Gerais Slsmentioning
confidence: 92%
See 3 more Smart Citations
“…In the work by Sousa, et al (2015), the oil from E. calycina leaves showed moderate cytotoxicity with CC50 137.4 μg/mL for HeLa cells, already in the work by Silva, et al (2021) showed an IC50 of 266.8 for HeLa cells, and an IC50 of 312.1 µg/mL for Vero cells within 24 h of exposure. Some oils have a toxic effect on MRC5 (human fibroblast) cells, such as oil from the leaves of E. flavescens DC.…”
Section: Goiás Minas Gerais Slsmentioning
confidence: 92%
“…Aegypti and later, the mortality events were quantified after 24 hours of exposure, with all tests being performed in triplicate, and having water and surfactant with negative controls. To assess larvicidal activity, the following criteria were used: LC50 ≤ 50 μg / mL is considered active, between 50 and 100 μg / mL, moderate activity, between 100 and 750 μg / mL of efficient or effective activity, and LC50 ≤ 750 μg / mL, inactive (Komalamisra, et al, 2005, Neves, et al, 2017Silva, et al, 2021).…”
Section: Larvicidal Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The extraction of the EO from each group of leaves was carried out in a Clevenger apparatus, by hydrodistillation, under reflux for 4 hours with 50 g of fresh leaves (Silva et al, 2020). The extraction was carried out in triplicate.…”
Section: Essential Oil Extractionmentioning
confidence: 99%